Role of oxidative stress in the pathogenesis of oral submucous fibrosis: A preliminary prospective study - G K Shakunthala; Rajeshwari G Annigeri; Shantala Arunkumar (Wolters Kluwer Medknow Publications, 2015)
Background: In the current scenario pathogenesis of majority of the diseases is deeply linked with the oxidative stress, irrespective of its etiology. Enumerable data suggests that reactive oxygen species play a key role in multistage carcinogenesis. Oral submucous fibrosis (OSMF) is considered as a potentially malignant disorder. Its increased incidence over recent years in the Indian subcontinent is a major health concern to oral physicians. However, the role of oxidative stress has not been widely investigated in OSMF. Aims: Is to evaluate both antioxidant and oxidant status in OSMF and to compare with controls. Settings and Design: Twenty patients and 20 controls of the same age group were enrolled in the study. Subjects and Methods: Five milliliters of blood were collected from each individual and serum was separated. Malondialdehyde (MDA) estimation using thiobarbituric acid (TBA) method, and antioxidant activity (AOA) using principle of TBA reactive substances was done using this serum, with a calorimetric method. Statistical Analysis Used: Student's t-test and ANOVA test. Results: The mean serum AOA status was seen to significantly decrease in OSMF patients, as compared to controls (P = 0.013). The increase in mean serum MDA level was highly significant in OSMF patients, as compared to controls (P < 0.001). Conclusion: The disparity between AOA and MDA levels in the patients clearly demonstrates the role of oxidative stress in the disease process. The results also suggest the use of antioxidants in the management of OSMF.